In-Vitro Bioequivalence of Paracetamol Tablets available in Syrian Market - دغمان براءه; هلا بركات; نسرين قدّار (Latakia University Journal -Medical Sciences Series, 2023)
Generic drugs are equivalent in range and absorption to the brand drug. Bioequivalence (BE) test is an essential requirement for interchanging brand and generic drugs, it should be carried out for all generic products, and it is evaluated In Vivo or In Vitro. Because in-vivo studies are expensive and complicated, the concept of In Vitro-In Vivo correlation (IVIVC) has been resorted to. Drugs which achieve (IVIVC) can be evaluated In Vitro only, one of these drugs is Paracetamol. This study aims to carry out BE test of Paracetamol tablets available in Syrian market (500 mg and 1000 mg). Tablets of four local companies A, B, C, D were tested and compared with the brand using dissolution test and calculating similarity and dissimilarity factor (f1 & f2). Other quality control tests were carried out. All tablets achieved weight and content uniformity and showed acceptable friability, with good hardness and a disintegration time of less than 30 minutes. For dissolution test, all tablets released more than 80 % Paracetamol within 30 minutes except A1 and B1 for 500 mg, and B3 for 1000 mg. Similarity and dissimilarity factor were calculated, and one company(C 500 mg) were bioequivalent with brand of the same dose. For 1000 mg tablets, both A and B3 batches showed bioequivalence with the brand.